Dinamika Perilaku Berbagi Anak Usia Dini Di TK Tunas Kusuma Bandar Lampung Tahun Pelajaran 2021/2022 - Rositi Rositi; Hetty Anggraini; Sulistianah Sulistianah (Early Childhood Research and Practice, 2022)
This study aims to describe sharing behavior and find out the factors that cause the difficulty of sharing in early childhood in Tunas Kusuma Kindergarten. This study uses a qualitative method. Sources of research data obtained from primary and secondary data. Primary data obtained from observations with students as the subject and secondary data from teacher interviews as informants and supporting data in the form of documentation. The data obtained were then collected, reduced, described and concluded. The results show that the dynamics of sharing or prosocial behavior in Tunas Kusuma Kindergarten have children who want to share and do not want to share. Most children want to share food with their friends and some children do not want to share. Children who are willing to share include children who are quick to adjust socially and have generosity. Family factors affect children not wanting to share. Parenting patterns as a model and source of children's prosocial behavior.